Determinants of unwillingness to practice farm forestry among households in the humid zone of Nigeria (2015)
Public sector dominance of forestry practices across the globe impedes realization of local and international forestry development targets despite huge local and international investments in the subsector. The need for private forestry practice as compliment to public initiatives on forestry development therefore becomes imperative. This paper reports the bottlenecks for private farm forestry practices among households in the humid zone of Nigeria where environmental hazards necessitate urgent tree planting initiatives. Groups/individuals with stakes in forestry were identified through stakeholder analysis across selected communities in Imo State, Nigeria. Relevant information was obtained using a set of questionnaire, which are supplemented with FGDs and IDIs. Baseline data on household forestry-based activities were obtained and analysed using Chi-square test of independence and logit regression models. Unwillingness by indigenous residents and local-based farmers was significantly influenced by their household sizes and conservation awareness. Traditional/religious leaders, landlords (landowners) in both communities surveyed correspondingly expressed resilience to propagate or condone forestry/conservation practices in their domain. Local-based farmers and indigenous residents in the study area expressed fear for any land use change that may contravene existing norms and practices. A robust and integrated grassroots’ motivation approach towards re-orientations of different categories of stakeholders’ mindset is therefore recommended to encourage private sector forestry entrepreneurship in the study area.